Continuing Development of Stroke Services using the Structured Judgement Review - Thomas, Jade Anne; Adie, Katja; Saw, Kyaw Lin (Cardiology and Cardiovascular Medicine, 2019)
The Royal Cornwall Hospitals Trust (RCHT) has undertaken a series of in-depth mortality reviews following publication of data demonstrating the trust to be an outlier for stroke associated mortality. This report of our 2017-18 data follows published outcomes and recommendations from the primary 2016-17 RCHT review. Our patients have high numbers of comorbidities, sustained moderate to severe strokes with a high hemorrhagic to ischemic stroke ratio. Patient care was reviewed using the Structured Judgement Review (SJR) process and care received was deemed as good to excellent in the majority of cases. Analysis of specific cases of low care scores has led to further recommended changes for local practice including; increased staffing levels on the stroke unit, increased number of hyperacute stroke beds, collaboration with primary care to prioritize AF detection and management, improved anticoagulation reversal processes within the emergency department and implementation of recommendations of national stroke guidelines for blood pressure control for haemorrhagic strokes.